Pembinaan Keluarga Sakinah di KUA Medan Denai : Analisis Qs. Ar-Rum Ayat 21 Perspektif Tafsir Al-Misbah - Juli Julaiha; Dwi Nova Ardani; Liza Aulia Br Manurung; Zukhruf Hafiz Rahimi; M. Rivan Febriansyah Harahap; Salsabila Nayla; Agustia Hilma (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This study examines the implementation of sakinah (tranquilty) family development at the religious affairs office (KUA) of Medan Denai subdistrict, North Sumatera Utara, Indonesia, trough the Qur'anic perspective of Surah Ar-Rum verse 21 as interpreted in Tafsir Al-Misbah by M. Quraish Shihab. The verse elucidates one of Allah's signs in creating spouses from among humankind to attain tranquility (sakinah), affection (mawaddah), and mercy (rahmah) within marital bonds. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews with religious counselors and newlywed couples, and documentation analysis of premarital counseling programs at KUA Medan Denai. Findings reveal that the office has integrated the triadic values of sakinah, mawaddah, and rahmah into its premarital guidance modules grounded in contextual Qur'anic interpretation. However, post-marital follow-up remains limited, affecting sustainability. Tafsir Al-Misbah provides a robust conceptual framework by interpreting sakinah as spiritual serenity rooted in faith, mawaddah as active emotional commitment, and rahmah as divine compassion manifested in daily family interactions. The study concludes that optimizing sakinah family development requires strengthening thematic Qur'anic-based counseling modules and establishing continuous post-nuptial mentoring to foster families that are spiritually grounded, emotionally resilient, and socially responsible. This research contributes to the discourse on integrating classical Qur'anic exegesis with contemporary family counseling practices in Indonesia's religious bureaucracy.